Alone : orphaned in the ocean - Logan, Richard D., 1942-; Fassbender, Tere Duperrault (Green Bay, Wis. : Titletown Pub., 2010)
Co-authored by a renowned psychologist and survival expert, this book delves into the details of how a little girl survived the at-sea murder of her family; the pod of whales who guarded her; and the aftermath and the recapturing of life
Includes bibliographical references and index
Keywords: Survival after airplane accidents, shipwrecks, etc. -- Biography; Victims of violent crimes -- United States -- Biography